Biometric and Structural Ocular Manifestations of Anterior Megalophthalmos - Chen, Tian-Hui; Chen, Ze-Xu; Zhang, Min; Chen, Jia-Hui; Lan, Li-Na; Jiang, Yongxiang (Frontiers in Medicine, 2022)
Objective: To examine the biometric ocular manifestations and structural ocular features of anterior megalophthalmos (AM). Methods: Fifteen patients with AM (30 eyes) from the Eye & ENT Hospital of Fudan University were included. The age-matched control group consisted of 30 participants (30 eyes) who underwent Pentacam HR and IOLMaster 700 measurements for one normal eye. Data on demographics, biometric manifestations, and genotypes were carefully compared. Results: A total of 15 patients with AM and 30 control patients were enrolled. There were no differences in age (37.27 ± 19.1 versus 31.43 ± 19.69 years, P = 0.249) between these 2 groups. AM eyes were characterized by premature cataracts (11/30, 36.67%) and zonular weakness with lens subluxation (22/30, 73.33%) compared to the control group. Twenty of the 30 AM eyes (66.67%) had significant posterior iris bowing and 16 of 30 AM eyes (53.33%) showed an enlarged ciliary ring on ultrasound biomicroscopy (UBM). Mean corneal curvature was lower in the AM eyes (42.01 ± 2.06 D versus 43.14 ± 1.38 D, P = 0.023). There was no significant difference in corneal pachymetry and central endothelial cell count between the AM and control groups. Significant differences were found in terms of the anterior chamber and white-to-white (WTW) among the Pentacam HR and IOLmaster 700 in patients with AM (P < 0.05). The difference was 0.53 ± 0.48 mm, and 0.36 ± 0.14 mm, respectively (P < 0.001). Conclusion: The results of this cohort study conclude the biometric and structural ocular manifestations of in Chinese cohorts. Posterior iris bowing (66.67%) and lens subluxation (73.33%) are the most characteristic findings in patients with AM with anatomical abnormalities of megalocornea and a deep anterior chamber, although corneal biometric manifestations of AM included flatter cornea and lower total corneal astigmatism. The knowledge of ocular manifestations of AM is important for diagnosis and preparation for the operation in advance to avoid intraoperative and postoperative complications. Significant differences were found in the anterior chamber and WTW values between the Pentacam HR and IOLMaster 700. Thus, we suggest that various examinations should be carefully considered before determining an AM diagnosis.